Psychometric evidence of a perception scale about covid-19 vaccination process in Peruvian dentists: a preliminary validation - César F. Cayo-Rojas; Nancy Córdova-Limaylla; Gissela Briceño-Vergel; Marysela Ladera-Castañeda; Hernán Cachay-Criado; Carlos López-Gurreonero; Alberto Cornejo-Pinto; Luis Cervantes-Ganoza (BMC, 2022)
Abstract Background In the current pandemic context, dental professionals have greater occupational risks due to their healthcare activity, placing their expectations on the vaccine as a means of protection and at the same time hoping that the immunization process will be safe, reliable and comfortable, giving them greater peace of mind when they return to work. Therefore, the aim of the present study was to develop and provide a preliminary validation of a scale to measure perception of the COVID-19 vaccination process in Peruvian dental professionals. Methods Cross-sectional study with instrumental design. The scale was self-administered virtually. It was distributed through social networks to 220 dental professionals from two universities in the Peruvian capital between June and August 2021. The Aiken V was used for content analysis, while descriptive statistics such as mean, variance, kurtosis and skewness were used for construct validation, in addition to Pearson's correlation matrix for analysis of the 18 items. Subsequently, a Parallel Analysis based on minimum rank factor analysis was performed. Finally, the reliability of the total scale and its dimensions was evaluated with Cronbach's alpha. Results The Aiken V coefficient values were favorable for all items. Parallel analysis indicated the existence of three dimensions. Principal component analysis with rotation suggested grouping eight items for the first dimension, six items for the second dimension and four items for the third dimension. These dimensions showed good reliability, as Cronbach's alpha was 0.87, (95% confidence interval [CI]: 0.84-0.90), 0.80 (95% CI: 0.75-0.84) and 0.82 (95% CI: 0.78-0.86), respectively. In addition, the overall reliability of the scale was 0.89 (95% CI: 0.86-0.91), being acceptable. Conclusions The perception scale of the COVID-19 vaccination process in dental professionals proved preliminarily to be a valid and reliable scale that can be used for research purposes. However, it is recommended to extend its application and evaluate its metric properties in other health professionals.